2013
DOI: 10.1186/1748-717x-8-232
|View full text |Cite
|
Sign up to set email alerts
|

Prone versus supine position for adjuvant breast radiotherapy: a prospective study in patients with pendulous breasts

Abstract: PurposeTo analyze dosimetric parameters of patients receiving adjuvant breast radiotherapy (RT) in the prone versus supine position.Methods and materialsForty-one out of 55 patients with pendulous breasts and candidates for adjuvant RT were enrolled in the study after informed consent. They underwent computed tomography (CT)-simulation in both prone and supine position. Target and non target volumes were outlined on CT images. Prescribed dose was 50 Gy delivered by two tangential photon fields followed by 10 G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(53 citation statements)
references
References 23 publications
2
50
1
Order By: Relevance
“…The prone mean heart NTD mean and mean LAD max doses were lower than those seen in standard free-breathing left breast radiotherapy [20], although confidence intervals overlap. Prone cardiac doses in this study were generally lower than reported in other studies comparing prone and supine treatments [11,21,22]. In keeping with the literature, mean lung doses were also significantly lower with prone treatment than supine treatment [9,11,23].…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…The prone mean heart NTD mean and mean LAD max doses were lower than those seen in standard free-breathing left breast radiotherapy [20], although confidence intervals overlap. Prone cardiac doses in this study were generally lower than reported in other studies comparing prone and supine treatments [11,21,22]. In keeping with the literature, mean lung doses were also significantly lower with prone treatment than supine treatment [9,11,23].…”
Section: Discussionsupporting
confidence: 65%
“…A possible reason for this is that MLC use or alteration of beam angles to avoid cardiac tissue is likely to result in relatively less WBCTV coverage compromise in larger-vs smaller-breasted women. Contrary to other published reports [21,24,25], this study demonstrates that it is possible to achieve comparable dose homogeneity for both techniques, but that to do so, more segments are required for supine treatment.…”
Section: Discussioncontrasting
confidence: 51%
“…This is the first study to analyse target and OAR dose compliance differences due to imaging modality (CT vs MRI) for target volume determination, in both supine and prone positions, although several groups have examined differences in supine and prone positioning for WB radiotherapy (Table 6) [13][14][15][16][17][18][19][20][21][22][23][24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…Some authors report that prone positioning is better at heart dose and/or volume sparing than supine [15-17, 20, 23]. Some have reported no significant difference in heart dose between prone and supine positions [19,22]. One group identified a significant benefit of prone positioning on heart doses for women where the WB_CTV exceeded 1000 cm 3 for WB radiotherapy [18].…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation